Paternal chromosome elimination of inducer triggers induction of double haploids in Brassica napus - Zhao, Shihui; Huang, Liangjun; Zhang, Qing; Zhou, Ying; Yang, Meicui; Shi, Haoran; Li, Yun; Yang, Jin; Li, Chao; Ge, Xianhong; Gong, Wanzhuo; Wang, Jisheng; et al. (Frontiers in Plant Science, 2023)
A synthetic octoploid rapeseed, Y3380, induces maternal doubled haploids when used as a pollen donor to pollinate plant. However, the mechanism underlying doubled haploid formation remains elusive. We speculated that double haploid induction occurs, as the inducer line's chromosomes pass to the maternal egg cell, and the zygote was formed through fertilization. In the process of zygotic mitosis, the paternal chromosome was specifically eliminated. Part of the paternal gene might have infiltrated the maternal genome through homologous exchange during the elimination process. Then, the zygote haploid genome doubled (early haploid doubling,EH phenomenon), and the doubled zygote continued to develop into a complete embryo, finally forming doubled haploid offspring. To test our hypothesis, in the current study, the octoploid Y3380 line was back bred with the 4122-cp4-EPSPS exogenous gene used as a marker into hexaploid Y3380-cp4-EPSPS, as paternal material to pollinate three different maternal materials. The fertilization process of crossing between the inducer line and the maternal parent was observed 48 h after pollination,and the fertilization rate reached 97.92% and 98.72%. After 12 d of pollination, the presence of cp4-EPSPS in the embryo was detected by in situ PCR, and at 13-23 d after pollination, the probability of F1 embryos containing cp4-EPSPS gene was up to 97.27%, but then declined gradually to 0% at 23-33 d. At the same time, the expression of cp4-EPSPS was observed by immunofluorescence in the3-29th day embryo. As the embryo development, cp4-EPSPS marker genes were constantly lost, accompanied by embryonic death. After 30 d, the presence of cp4-EPSPS was not detected in surviving embryos. Meanwhile, SNP detection of induced offspring confirmed the existence of double haploids. Further indicating that the induction process was caused by the loss of specificity of the paternal chromosome. The tetraploid-induced offspring showed infiltration of the induced line gene loci, with heterozygosity and homozygosity. Results indicated that the induced line chromosomes were eliminated during embryonic development, and the maternal haploid chromosomes were synchronously doubled in the embryo.These findings support our hypothesis and lay a theoretical foundation for further localization or cloning of functional genes involved in double haploid induction in rapeseed